2015
DOI: 10.1016/j.wace.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil moisture on extreme maximum temperatures in Europe

Abstract: Land-atmosphere interactions play an important role for hot temperature extremes in Europe. Dry soils may amplify such extremes through feedbacks with evapotranspiration. While previous observational studies generally focused on the relationship between precipitation deficits and the number of hot days, we investigate here the influence of soil moisture (SM) on summer monthly maximum temperatures (TXx) using water balance model-based SM estimates (driven with observations) and temperature observations. General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
136
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 53 publications
2
136
0
Order By: Relevance
“…9b). Various studies have demonstrated the role of precipitation deficit in spring for hot temperature extremes in summer (Mueller and Seneviratne 2012;Whan et al 2015). We have analysed precipitation and soil moisture changes in spring season (MAM) in response to AAer changes and results indicate that there are no significant pre-summer soil moisture anomalies that persist into summer (not shown).…”
Section: Response To the Direct Impact Of Changes In Aaer Precursor Ementioning
confidence: 99%
See 3 more Smart Citations
“…9b). Various studies have demonstrated the role of precipitation deficit in spring for hot temperature extremes in summer (Mueller and Seneviratne 2012;Whan et al 2015). We have analysed precipitation and soil moisture changes in spring season (MAM) in response to AAer changes and results indicate that there are no significant pre-summer soil moisture anomalies that persist into summer (not shown).…”
Section: Response To the Direct Impact Of Changes In Aaer Precursor Ementioning
confidence: 99%
“…The shift towards higher sensible heat fluxes in turn produces drier and warmer air and increases evaporative demand, which dries the soil further (Mueller and Seneviratne 2012;Boé and Terray 2014;Miralles et al 2014;Cattiaux et al 2015;Whan et al 2015). This positive feedback loop generates less cloud and increased surface SW radiation, which again causes even more drying, illustrating the importance of soil processes in driving the regional responses of temperature and temperature extremes (Dai et al 1999;Jaeger and Seneviratne 2011;Mueller and Seneviratne 2012;Stegehuis et al 2012;Whan et al 2015) and resulting in increases in T max , TX x , and the frequency in summer days as well as an enhancement of DTR (Fig. 9b).…”
Section: Response To the Direct Impact Of Changes In Aaer Precursor Ementioning
confidence: 99%
See 2 more Smart Citations
“…The combination of high temperatures and droughts initiate a positive regional feedback mechanism: the precipitation deficits and enhanced evaporative demand generally associated with warm spells (e.g. atmospheric blockings) triggers soil moisture deficit, thus suppressing evaporative cooling (Teuling et al, 2013) and leading to hotter and drier conditions if soil moisture becomes limiting for evapotranspiration (Whan et al, 2015). Trnka et al (2015b) concluded that increased global radiation and air temperature together with decreased relative humidity led to increase of reference evapotranspiration in all month of the growing season (particularly in April, May and August) over the CR.…”
Section: Introductionmentioning
confidence: 99%